Proove in Kleene algebra the term a*=(aa)*+a(aa)*

Please someone, who knows the Kleene algebra.  I must prove that the term (aa)*+a(aa)* equals a*. Can anybody help me? There are some theorems, what you must use. In that attached PDF are the theorems
corthezzAsked:
Who is Participating?
I wear a lot of hats...

"The solutions and answers provided on Experts Exchange have been extremely helpful to me over the last few years. I wear a lot of hats - Developer, Database Administrator, Help Desk, etc., so I know a lot of things but not a lot about one thing. Experts Exchange gives me answers from people who do know a lot about one thing, in a easy to use platform." -Todd S.

Brian UtterbackPrinciple Software EngineerCommented:
I don't see an attached PDF file.
0
corthezzAuthor Commented:
The solution is somewhere in the PDF
oporaTCS.pdf
0
Brian UtterbackPrinciple Software EngineerCommented:
I need a little clarification on the use of the "+" here. In regular expressions, the "+" operator is used to designate "one or more",
which is to say formally:

a+ <=> aa*

It can also be used to designate concatenation, that is
a+b <=> ab

And it can also be used to designate the union of two sets:

A + B <=>  A union B

Can you say which usage is meant here?  
0
Cloud Class® Course: Microsoft Exchange Server

The MCTS: Microsoft Exchange Server 2010 certification validates your skills in supporting the maintenance and administration of the Exchange servers in an enterprise environment. Learn everything you need to know with this course.

corthezzAuthor Commented:
union

take a look at pages 10, 11, 14, 38, 39,40... near these pages are the answers in attached PDF
0
corthezzAuthor Commented:
a* = U A^n, where n >= 0
0
corthezzAuthor Commented:
i must get the prove in Kleene algebra or in regular expressions
0
NovaDenizenCommented:
let X = (aa)* + a(aa)*
To prove equivalence with a*, you need to show X <= a* and a* <= X.

I suspect this might be schoolwork, so I'll only do the first half. :)
a* = a*
a* = a* + a*
by definition of <=
a* <= a*
note that for any X, X <= X.
apply A.10 twice
1 + aa* <= a*
1 + a + aaa* <= a*
(1 + a) + (aa)a* <= a*
by A.12
(aa)*(1+a) <= a*
(aa)* + (aa)*a <= a*
by R.17
(aa)* + a(aa)* <= a*
X <= a*

Now just prove a* <= X similarly.  Start with X <= X, then get to an application of A.12 that results in a*1 <= X.  Once that's done, you can conclude that a* = X.
0

Experts Exchange Solution brought to you by

Your issues matter to us.

Facing a tech roadblock? Get the help and guidance you need from experienced professionals who care. Ask your question anytime, anywhere, with no hassle.

Start your 7-day free trial
corthezzAuthor Commented:
Thank you! This is what i looked for....... btw i must completed it until today 18:00 ;)
0
It's more than this solution.Get answers and train to solve all your tech problems - anytime, anywhere.Try it for free Edge Out The Competitionfor your dream job with proven skills and certifications.Get started today Stand Outas the employee with proven skills.Start learning today for free Move Your Career Forwardwith certification training in the latest technologies.Start your trial today
Math / Science

From novice to tech pro — start learning today.

Question has a verified solution.

Are you are experiencing a similar issue? Get a personalized answer when you ask a related question.

Have a better answer? Share it in a comment.